2007
DOI: 10.1007/s00420-007-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions, adverse events and mental health problems in a sample of 949 German teachers

Abstract: To be a teacher is a hard work and requires coping of considerable amount of adverse events. Based on the GHQ, nearly 30% of teachers suffer from significant mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 24 publications
12
114
1
9
Order By: Relevance
“…The work time of a regular teacher working full time and in addition with other responsibilities exceeds the amount of a normal work week and reaches at least 51 hours per week. This overtime work is due to extra tasks teachers have, like preparing for classes, checking tests and other work positions (Bauer et al, 2007). The fact that most forestry, construction and agricultural workers work overtime is consistent with findings in other studies, for example, in a study about work-family conflicts it was found that 76.3% respondents working in construction work overtime (Tarek et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The work time of a regular teacher working full time and in addition with other responsibilities exceeds the amount of a normal work week and reaches at least 51 hours per week. This overtime work is due to extra tasks teachers have, like preparing for classes, checking tests and other work positions (Bauer et al, 2007). The fact that most forestry, construction and agricultural workers work overtime is consistent with findings in other studies, for example, in a study about work-family conflicts it was found that 76.3% respondents working in construction work overtime (Tarek et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Violence in educational and public administration work is a major risk factor recognised also in other studies. Studies have shown that pupils and their parents are usually the ones who cause violence (Bauer et al, 2007;Fox and Stallworth, 2010;Tiesman et al, 2013). No significant difference was found between industries and their groups in this question and none of the respondents in industry Group 2 responded affirmatively to this question, making it difficult to compare the results with other studies.…”
Section: Discussionmentioning
confidence: 68%
“…Na Alemanha, concomitantemente à elevada carga de trabalho, ressaltou-se uma proporção elevada dos sujeitos avaliados com relatos de vivências de indultos, ameaças, atos de vandalismo cometidos pelos alunos. Ademais, os pais foram mencionados como fonte de eventos adversos no ambiente da escola (Bauer et al, 2007).…”
Section: Dimensões Da Intensificação Do Trabalho Docenteunclassified
“…• The increasing working load (more than 51 hours weekly when full time employed) German teachers face (Bauer et al 2007). As findings by Esslinger (2002) and Hildebrandt (2008) show, almost all teachers who took part in their respective research studies claimed lack of time as one major obstacle to get involved into innovative subjects or school development processes.…”
Section: Germanymentioning
confidence: 99%